Assessment of antibodies in the upper and lower human respiratory tract at steady state and after respiratory viral infection - Marios Koutsakos; Jackson S Turner; M Cristina Vazquez Guillamet; Daniel Reynolds; Tingting Lei; Derek E Byers; Ali H Ellebedy; Philip A Mudd (Clinical & Translational Immunology, 2023)
Abstract Objectives There is an increasing appreciation for the need to study mucosal antibody responses in humans. Our aim was to determine the utility of different types of samples from the human respiratory tract, specifically nasopharyngeal (NP) swabs obtained for diagnostic purposes and bronchoalveolar lavage (BAL) obtained in outpatient and inpatient settings. Methods We analysed antibody levels in plasma and NP swabs from 67 individuals with acute influenza as well as plasma and BAL from individuals undergoing bronchoscopy, including five control subjects as well as seven moderately and seven severely ill subjects with a respiratory viral infection. Levels of α2‐macroglobulin were determined in BAL and plasma to assess plasma exudation. Results IgG and IgA were readily detectable in BAL and NP swabs, albeit at different ratios, while IgM levels were low. The total amount of antibody recovered from NP swabs varied greatly between study participants. Accordingly, the levels of influenza HA‐specific antibodies varied, and individuals with lower amounts of total Ig in NP swabs had undetectable levels of HA‐specific Ig. Similarly, the total amount of antibody recovered from BAL varied between study participants. However, severely ill patients showed evidence of increased plasma exudation, which may confound analysis of their BAL samples for mucosal antibodies. Conclusion Nasopharyngeal swabs collected for diagnostic purposes may have utility in assessing antibodies from the human nasal mucosa, but variability in sampling should be accounted for. BAL samples can be utilised to study antibodies from the lower respiratory tract, but the possibility of plasma exudation should be excluded.